Reproductive Performance of Orange Mud Crab, Scylla Olivacea (Herbst), Broodstock Fed Selected Foods - Misieng, Josephine Dorin (2007)
This study was conducted to investigate the effects of selected food on the growth, ovarian development and ovarian maturity of the unilaterally eyestalk-ablated and unablated Scylla olivacea bloodstock over 84 days in captivity. In this 2-factorial experiment, chopped trash fish, chopped cuttlefish and shelled prawn were fed twice daily at 5% of biomass o unablated and unilaterally eyestalk-ablated immature female S. olivacea. Mortality and moulting were recorded daily. The measurements of the mud crabs’ body weight, carapace width and ovarian biopsy were recorded weekly. Food and unilateral eyestalk ablation had significant effects on the growth of the S. olivacea broodstock, in terms of body weight and carapace width gain. Chopped trash fish performed at par with chopped cuttlefish for the growth of the broodstock while the unilateral eyestalk ablation gave a superior growth to normal broodstock in terms of body weight and carapace width gain.The interaction of food and eyestalk ablation had significant effects on the duration of Stage II and III of the ovarian development with shelled prawn and unilaterally eyestalk ablation appeared to give the shortest period of ovarian development in the broodstock (10.1 days of Stage II and 10.9 days of Stage III). The effects of food, eyestalk ablation and their interactions were not significant on the ovarian maturity but food had significant effects on the ovarian development after the first mating. Chopped cuttlefish showed significantly better effects for the broodstock to reach the Stage IV of ovarian maturity after mated. Female mud crabs fed with chopped trash fish resulted in 66.64% mating while those fed with chopped cuttlefish showed 83.28% of mating success. Both diets showed significantly better effects in promoting mating process of the broodstock. Apparently, S. olivacea matures at a much smaller size than S. serrata, S. paramamosain and slightly smaller than S. tranquebarica. The broodstock needs diets of different nutritional values for their growth at different phases of ovarian development and maturity.